Rigid Body Assembly Impact Models for Adiabatic Cutoff Equipments - MASSENZIO, M.; PASHAH, S.; JACQUELIN, E.; BENNANI, A. (Engineering Transactions, 2008)
This paper is concerned with systems consisting of components colliding with each other. In particular, a high velocity adiabatic impact cutoff machine is investigated. For general understanding of the impact dynamics (affected by a large number of parameters), the mechanisms are modelled in a simplified and accurate manner. Two simple models are developed: the energy-balance model and the spring-mass model. The energy-balance model is based on the principle of total energy conservation. It provides only the punch minimum kinetic energy required for efficient cutting. Concerning the spring-mass model, the different components are represented by rigid masses and their deformations are modelled by springs (linear or nonlinear in the case of contact stiffness). The resulting non-linear equations are solved using the Newmark numerical technique. The impact force, velocity, displacement and acceleration histories are calculated what makes possible a fine description of the cutoff cycle steps. The two models are helpful for both the design and tuning of the mechanisms involving impacts between their components.